The impact of TMpoint service quality on the customer satisfaction at TMpoint Setapak / Noor Shazila Mohd Alias - Mohd Alias, Noor Shazila (Faculty of Business and Management, 2006)
This study focuses on " The Impact of TMpoint Service Quality on the Customer Satisfaction". The objectives of the study are to analyze the respondent's level of satisfaction towards service quality of TMpoint, to identify which factors of TMpoint service quality such as people, process and facilities will highly influence customer satisfaction and also to determine whether the respondent's gender, age and monthly income influence their satisfaction level towards TMpoint service quality in term of facilities.